Pelatihan Pembuatan Pupuk Berbahan Eco-Enzyme Sebagai Upaya Mendukung Pertanian Terintegrasi - Sri Indaryati; Eny Ivan’s; Novita Novita; Novia Ambar Sari; Wintari Mandala (Jurnal Nusantara Mengabdi, 2026)
Purpose: This community service activity aims to improve the knowledge and skills of members of the Orchid Women Farmers Group (KWT) in Tegal Yoso Village in processing household organic waste into liquid organic fertilizer made from eco-enzymes to support the integrated farming system of the Garden-Cage-Pond pattern.Research Methodology: The method used is Participatory Rural Appraisal (PRA) through the stages of problem identification, counseling, Focus Group Discussion (FGD), demonstration, practice of making eco-enzymes, and  pre-test and post-testResults: The results of the activity showed that the training was able to improve the knowledge and skills of participants in the manufacture and application of eco-enzyme fertilizersConclusions:. The evaluation showed that 80% of participants were in the category of very understanding, 15% understood, and 5% understood enough after the training, while there were no more participants in the category of not understanding or not understanding.Limitations: In addition to enhancing participant capacity, this activity produces a liquid organic fertilizer made from eco-enzymes ready for use in plant cultivation and encourages the productive use of organic waste.Contributions: This program contributes to supporting environmentally friendly integrated agriculture, increasing the independence of farmer groups, and can be replicated in other communities with similar characteristics.